A Celebration of the 25th Anniversary of the American Chemical Society Publication, "The Journal of Inorganic Chemistry" - American Chemical Society (1986)
Speakers at a dinner celebrating the 25th anniversary of the Journal of Inorganic Chemistry, held at the 192nd American Chemical Society (ACS) National Meeting. Remarks at this lively event mostly focus on the history of the journal and recognition of people involved in its publication. Speakers include: M. Frederick (Fred) Hawthorne; Robert (Bob) Parry; Edward (Ed) King; George Pimentel; Stephen Lippard; Galen Stucky; Herbert (Herb) Kaesz; Duward F. Shriver; Edward (Ed) Solomon; and D. H. Michael (Mike) Bowen.
Keywords: American Chemical Society; Chemistry, Inorganic; Chemistry, Inorganic--Research; Periodicals; Chemistry--Periodicals; Hawthorne, M. Frederick; Parry, Robert W. (Robert Walter), 1917-; King, Edward L. (Edward Louis), 1920-; Pimentel, George C.; Lippard, Stephen J.; Stucky, Galen D., 1936-; Kaesz, Herbert D.; Shriver, D. F. (Duward F.), 1934-; Bowen, D. H. Michael; Congresses and conventions